2016
DOI: 10.1037/rep0000071
|View full text |Cite
|
Sign up to set email alerts
|

A survey of psychology practice in critical-care settings.

Abstract: The findings indicate that health-service psychologists are involved in critical-care settings and in various roles. A more broad-based survey of hospitals across the United States would be required to identify how frequently health-service psychologists are consulted and what specific services are most effective, valued, or desired in critical-care settings. (PsycINFO Database Record

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
14
0
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(15 citation statements)
references
References 25 publications
(28 reference statements)
0
14
0
1
Order By: Relevance
“…Despite this, presence of psychology in the ICU setting remains scarce with only 17% of responding units offering psychological services [ 17 ]. In the United States, a survey of the American Psychological Association list serve’s practicing psychologists identified 51 individuals who provide cognitive assessments, family support, education, behavioral management, psychotherapy, and/or suicide risk assessments in critical care settings [ 18 ]. Limited outcome data is available to date, however.…”
Section: Discussionmentioning
confidence: 99%
“…Despite this, presence of psychology in the ICU setting remains scarce with only 17% of responding units offering psychological services [ 17 ]. In the United States, a survey of the American Psychological Association list serve’s practicing psychologists identified 51 individuals who provide cognitive assessments, family support, education, behavioral management, psychotherapy, and/or suicide risk assessments in critical care settings [ 18 ]. Limited outcome data is available to date, however.…”
Section: Discussionmentioning
confidence: 99%
“…Psicologia ▪ Suporte psicológico e/ou psicoeducação com familiares (30,31) ; ▪ Avaliações cognitivas e neuropsicológicas (30) ; ▪ Assistência psicológica ao paciente, com intervenções de apoio e orientação (31) ;…”
Section: Nutriçãounclassified
“…A comprehensive review of this topic would far exceed space limitations; therefore, the focus is on brief summarizations designed to point the way to a more directed and in-depth study for the interested reader. Although we are aware that a survey recently demonstrated that psychologists from several specialty backgrounds (i.e., health, rehabilitation, and neuropsychology) are involved in critical care settings (Stucky, Jutte, Warren, Jackson, & Merbitz, 2016), for the purposes of this chapter, we have elected to focus on a discussion of specific implications for rehabilitation psychologists with hope that it might stimulate critical thinking about evolving roles, activities, opportunities, and issues for that specialty. Admittedly, the foundational principles of health, rehabilitation, and neuropsychology are similar in that they all emphasize the application of the biopsychosocial model in medical settings.…”
Section: Kirk Stucky and Ann Marie Warrenmentioning
confidence: 99%
“…This paper is now referenced as a supplemental reading in the chapter on rehabilitation in Resources for Optimal Care of the Injured Patient published by the American College of Surgeons Committee on Trauma (2014, p. 93). It also is interesting to note that in a recent survey, psychologists who worked in critical care settings at least monthly were more likely to be at a Level I or pediatric trauma center, and a higher proportion of rehabilitationoriented providers provided intensive care, critical care, and neurointensive care services relative to nonrehabilitation-oriented providers (Stucky et al, 2016). This trend may be related to the unique skills that rehabilitation-oriented psychologists possess.…”
Section: The Development and Expansion Of Level I Trauma Centersmentioning
confidence: 99%